Peran Jam’iyah Shalawat Diba’ Kubra Terhadap Kerukunan Masyarakat Desa Sawiji Kecamatan Jogoroto Kabupaten Jombang - Shudur, Mishbahush; Samani, Samani (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2023)
This research aims to find out empirical and comprehensive information about the role of Jam'iyah Shalawat Diba' Kubra which is a forum for the community to build relationships in achieving harmony in Sawiji Village, Jogoroto District, Jombang Regency. This jam'iyah uses the traditional al-Banjari musical instrument, a traditional musical instrument that is played by hand and contains keys with the terms